Prevalence of hemoglobinopathies detected by high performance liquid chromatography in tertiary care centre, Kota, Rajasthan - Pathak, Vandana; Sharma, Ila; Agrawal, Akshat; Mund, Poonam (International Journal of Advances in Medicine, 2024)
Background: Hemoglobinopathies are the most common heterogeneous group of monogenetic disorder in the world. Their prevalence varies with geographical regions. India is developing country and many studies have shown a significant burden of hemoglobinopathies in India. Our aim is to estimate prevalence of various hemoglobinopathies in our region. Methods: The present study was conducted at the department of pathology, Government Medical College, Kota on patients referred for antenatal or voluntary premarital checkup, patients with clinical history and complete blood count (CBC) suggestive of hemolytic anemia, and family members of known cases of hemoglobinopathies. Transfusion-dependent patients were also included. However, patients with history of blood transfusion within the last 1 month were excluded. EDTA samples were used for CBC using 6-part differential cell counter and high-performance liquid chromatography (HPLC) using BIORAD D10 analyzer. The results were tabulated and analyzed. Results: Of the 226 cases studied, 139 (61.5%) were females and 87 (38.5%) were males. Most common age group was 21 to 30 years. The number of thalassemia traits were 26 (11.5%), sickle cell traits were 7 (3.1%), sickle cell homozygous was 1 (0.4%), compound heterozygous for sickle cell and thalassemia were 2 (0.9%), while the remaining 190 patients (84.07%) were found to have normal HPLC, with presence or absence of nutritional deficiency. Conclusions: In our study, we found a high prevalence of hemoglobinopathies among patients. The most common disorder detected was beta thalassemia trait. Most of the hemoglobinopathies found in our study could be accurately quantified by HPLC which is a rapid, sensitive, and reproducible method for the detection of different hemoglobinopathies.